METHODS USED BY WOMEN PARLIAMENTARIANS TO INFLUENCE LEGISLATIVE PROCESSES AND OUTCOMES IN KENYA'S NATIONAL ASSEMBLY OF THE 11TH PARLIAMENT (2013 -2017) - Miruka, Simon Okumba; Ngare, Grace Wamue; Okemwa, Pacificah (International Journal of Gender Studies, 2021)
Purpose: The study examined the legislative influence of women in the context of gender quotas in Kenya's National Assembly of the 11th parliament (2013-207). This article focuses on the methods women parliamentarians used to assert legislative influence. Methodology: This was a descriptive case study which focused on all 68 women in the National Assembly. Respondents were identified through stratified sampling based on: pathway to parliament; membership and leadership of parliamentary structures; contribution to debate; and sponsorship of Bills enacted. A total of 11 women were interviewed, derived from four of the seven parliamentary political parties, specifically the two largest political coalitions which contributed 94% of the legislature. The study also interviewed four purposively sampled key informants (KIs) - three male and one female. The data was processed manually, analysed and presented under each study objective. Sources of primary data were coded as follows: WL (Woman Legislator), ML (Male Legislator) and KI (Key Informant). All respondents were allocated specific numbers for identification and acknowledgement. Findings: The study established that women legislators used the following methods to influence legislation: mobilisation of male colleagues; solidarity across political parties; activism; leveraging committee positions; reliance on the National Assembly leadership; and compromise and conciliation. It notes that the methods were effective in some circumstances but failed in others. Unique contribution to theory, practice and policy: The study outlines how various methods were applied by women legislators in Kenya's National Assembly 2013-2017, the first time quotas were applied in Kenyan elections. It fills the gap in earlier studies that did not document these methods. The study notes that the methods were not intrinsically weak but their effectiveness was limited by circumstances, especially the attitude of male legislators. It illustrates the importance of diversifying approaches to influence legislation. The study recommends that women legislators should: work with supportive male legislators and other pressure groups in the legislature; introduce Bills early in the legislative calendar to improve chances of success; receive training on parliamentary work; and occupy influential parliamentary leadership positions.